Influence of Platelet Count on Haemostatic Plug Formation and Plug Stability - Bergqvist, D; Arfors, K.-E (Thrombosis and Haemostasis, 1973)
The initial haemostatic process in thrombocytopenic animals after transection of arterioles and venules was investigated in a rabbit mesenteric preparation. Graded thrombocytopenia with a bone marrow suppressant (busulphan) and anti-platelet serum gave comparable results. With decreasing platelet counts there was progressive prolongation in haemostatic plug formation time, and a significant non-linear relation between platelet count and haemostatic plug formation time. Haemostatic plugs formed under thrombocytopenic conditions were more stable than normal. The difference in stability normally seen between plugs in arterioles and venules disappeared with decreasing platelet counts. The relationship between venular and arteriolar haemostatic plug formation time was also reduced with decreasing platelet counts.